2016
DOI: 10.1002/smll.201502109
|View full text |Cite
|
Sign up to set email alerts
|

Subcompartmentalized Nanoreactors as Artificial Organelle with Intracellular Activity

Abstract: Cell mimicry is an approach which aims at substituting missing or lost activity. In this context, the goal of artificial organelles is to provide intracellularly active nanoreactors to affect the cellular performance. So far, only a handful of reports discuss concepts addressing this challenge based on single-component reactors. Here, the assembly of nanoreactors equipped with glucose oxidase (GOx)-loaded liposomal subunits coated with a poly(dopamine) polymer layer and RGD targeting units is reported. When co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…However, artificial organelles outperform by conducting multiple reactions in parallel confined within separated subunits while avoiding undesired reactions . A solitary example reported by Thingholm et al has shown catalytic activity by making use of a carrier containing multiple compartments . The authors reported a nanoreactor consisting of liposome‐decorated silica particles encapsulating the enzyme glucose oxidase which is able to convert glucose into d ‐glucano‐1,5‐lactone and hydrogen peroxide (H 2 O 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, artificial organelles outperform by conducting multiple reactions in parallel confined within separated subunits while avoiding undesired reactions . A solitary example reported by Thingholm et al has shown catalytic activity by making use of a carrier containing multiple compartments . The authors reported a nanoreactor consisting of liposome‐decorated silica particles encapsulating the enzyme glucose oxidase which is able to convert glucose into d ‐glucano‐1,5‐lactone and hydrogen peroxide (H 2 O 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Capsosomes could function as an extracellular microreactor in the presence of endothelial intestinal cells and under the effect of a peristaltic flow, mimicking the dynamic environment of the intestine. While the three multiple‐compartment carriers have been successfully employed to conduct enzymatic reactions, liposome‐coated silica particles remain as a solitary example of carriers containing multiple compartments with reported enzymatic activity intracellularly . Nonetheless, the concept of sub‐compartmentalization has never been considered to perform multiple enzymatic reactions in a parallel manner inside the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, catalytic activity has also been demonstrated for capsosomes entrapping not only liposomes but also polymeric capsules as inner compartments . Importantly, the enzymatic activity of capsosomes can be preserved for several subsequent cycles, i.e., the capsosomes could be reused; and can also be retained in the presence of cells or when acting inside the cells as intracellularly active microreactors, which will be explained in detail in section .…”
Section: Multicompartment Carriersmentioning
confidence: 99%
“…Although the potential of multicompartment systems as microreactors has been reported in literature, it has not been until recently that their applicability as artificial organelles has been demonstrated. The firsts to show preserved enzymatic activity employing a multicompartment carrier in an intracellular environment were Stadler and co‐workers . The authors adsorbed GOx‐loaded liposomes onto a silica particle that was subsequently coated with a PDA shell functionalized either with PEG or with the targeting moiety arginylglycylaspartic (RGD).…”
Section: Intracellular Functionalitymentioning
confidence: 99%
“…To this end, recently,a considerable efforth as been directed into the development of promising artificial organelles that can effectively accomplish parallel multicascade reactions in aw ay similar to naturalo rganelles. [34] Particularly for therapeutic applications, several attempts have been made to develop therapeutic nanoreactors that can perform multistep (chemo)biologicalr eactions to treat variousd iseases including cancer.F or example, Palivan et al [35] reported an enzymatic cascades ystem conducted inside the cavities of polymeric nanocontainers that can be used as an effective approach to detect and combato xidative stress, which is one of the pathological factors in various diseases ranging from arthritis to cancer. In their reported treatment concept, they used SOD and lactoperoxidase( LPO) as the model of enzymes that act in tandem and these wereco-encapsulated into the cavity of single-compartmentv esicular nanocontainert o complementary convert superoxide radicals to molecular oxygen and water.S imilar treatment concepts,b ut with different paired catalytic enzymes or typeo fn anocontainers have also been reported in the literature.…”
Section: Multiple-enzyme-(cascade Reactions)-based Therapeutic Nanorementioning
confidence: 99%